Five-Factor Personality Inventories Have a Competence-Related Higher-Order Factor Due to Item Phrasing - Bäckström, Martin; Björklund, Fredrik; Persson, Rebecka; Costa, Ariela (Frontiers in Psychology, 2020)
This research examines the items of some of the most well established five-factor inventories. Results reveal that both experts and laymen can distinguish between items that refer to how competently a behavior is performed and items that do not (Study 1). Responses to items that refer to competence create a higher-order factor in the personality inventories (Study 2), and the variability in responses to competence related items in personality self-ratings is best modelled as general factor rather than as also tied to the specific Big Five factors (Study 3 and 4). We suggest that a focused debate on what a personality items should refer to is likely to have considerable positive consequences for both theory and measurement or of personality.